They Dare Disturb the Universe - Awale, Rasha (Hungarian Journal of English and American Studies, 2020)
Book review:Kauffman, L. A.  Direct Action: Protest and the Reinvention of American Radicalism. London: Verso, 2017. 236 pages. ISBN 978-1-78478-409-6. Pbk. $12.